PEMBERIAN CHEST PHYSIOTHERAPY DAN LATIHAN PERNAPASAN PADA PASIEN DEWASA DENGAN PNEUMONIA KOMUNITAS RINGAN DAN RETENSI SPUTUM: A CASE REPORT - Puspita, Diah; Dharmajayanti, Ida Ayu Laksmi; Yasa, Kadek Andre; Hartaningrum, Dewa Ayu Putri; Prasana, I Gede Eka Juli; Dewi, Dewa Ayu Kadek Ari Purnama; Jeviana, Ariezta (Forind Press, 2025)
Community Acquired Pneumonia is a major cause of lower respiratory tract disease. Non-severe cases are usually managed without hospitalization, but sputum retention can delay recovery. This case report describes the role of respiratory physiotherapy in a mild pneumonia patient with sputum retention. A 43-year-old male underwent three physiotherapy sessions including infrared therapy, chest physiotherapy, effective coughing, and breathing exercises. After treatment, dyspnea decreased from Borg scale 3 to 2, thoracic expansion improved, and vital signs remained stable. Physiotherapy interventions effectively facilitated sputum clearance, improved ventilation, and enhanced breathing efficiency.